Motorcycle security system based on Internet of Things (IoT) - Ikhwan, Rezky; Dewi, Citra (Journal of Industrial Automation and Electrical Engineering, 2024)
In response to the increasing cases of motorcycle theft, a more advanced and reliable security system is needed. This research aims to design and build a motorcycle security system integrated with Internet of Things (IoT) technology. The system combines the use of a microcontroller, RFID module, GSM/GPRS/GPS module within the SIM808, relay, servo motor, and vibration sensor to create an effective security solution. With the implementation of IoT, this system allows motorcycle owners to monitor the vehicle’s position in real-time through a smartphone application. The GPS module provides accurate coordinate information, while the GPRS modules facilitate communication using internet for data transmission. The relay functions to cut off the power supply to the vehicle’s engine, turn the servo motor on and off, and activate and deactivate the buzzer, thus preventing motorcycle theft. The software used include Blynk for use on the user’s smartphone. Testing shows that the motorcycle security system prototype is effective using Blynk application for long-range, with a time of 1 to 2 seconds to receive and process commands